Relationship of Serum Trimethylamine N-Oxide Levels With Carotid Intima-Media Thickness and Disease Activity in Psoriasis Patients - Zekey, Emre; Tunçez Akyürek, Fatma Tunçez Akyürek; Tunçez, Abdullah; Akyürek, Fikret; Doğan, Merve Ezgi (Dermatology Practical & Conceptual, 2023)
Introduction:  Psoriasis is an inflammatory disease that can cause cardiovascular comorbidities. Some recent studies have indicated that impaired gut microbiota and metabolites may be associated with inflammatory diseases.Objectives: In this study, the relationship between serum trimethylamine n-oxide (TMAO, a gut bacterial metabolite) level and carotid intima-media thickness (CIMT) and disease severity in psoriasis patients was investigated.Methods: Age- and gender-matched 73 patients and 72 healthy controls were included in the study. In both groups serum trimethylamine n-oxide(TMAO), oxidized low- density lipoprotein (ox-LDL), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), triglyceride, total cholesterol, high-sensitivity C-reactive protein (hs-CRP), creatinine, aspartate aminotransferase (AST) and alanine aminotransferase(ALT) levels were recorded and the carotid intima-media thickness (CIMT) was measured by B-mode ultrasonography by a cardiologist. Results: TMAO, hs-CRP, oxidized-LDL, triglyceride and CIMT levels were statistically higher in the patient group. HDL levels were statistically higher in the control group. There was no significant difference between the two groups in terms of total cholesterol and LDL-C levels. In partial correlation analyzes in the patient group, positive correlations were observed between TMAO and CIMT, LDL-C and total cholesterol levels. Linear regression analysis showed that TMAO levels positively predicted CIMT levels.Conclusions: This study confirmed that psoriasis is a risk factor for the development of cardiovascular disease and that elevated serum TMAO levels in these patients indicate the presence of intestinal dysbiosis. Furthermore, TMAO levels were found to be a predictor of the risk of developing cardiovascular disease in psoriasis patients.